PE PENGARUH PERSEPSI DAN PENGETAHUAN PERPAJAKAN TERHADAP MINAT KARIR MAHASISWA AKUNTANSI SEBAGAI AKUNTAN PAJAK - Uswatun Hasannah; Permata, Amelia (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This study aims to determine the effect of perception and knowledge of taxation on the career interests of accounting students in choosing to be tax accountants. This study uses quantitative methods and primary data from sampling active accounting students at the State University of Surabaya. Data collection in this study was carried out through the distribution of Google Form questionnaires using purposive sampling techniques, which obtained data from 75 respondents. Data analysis used multiple linear regression test. The results of this study indicate that perception and knowledge of taxation have a partial and simultaneous effect on the career interests of accounting students to become tax accountants. Keywords: Perception; Tax Knowledge; Career Interest of Accounting Student; Tax Accountant